Depressive symptoms in involuntary hospitalized patients in Cyprus: Socio-demographic and psychopathological characteristics - Kaikoushi, Katerina; Karanikola, Maria; Middleton, Nicos; Chatzittofis, Andreas; Nystazaki, Maria; Bella, Evanthia; Stylianou, Constantinos; Kinnis, Evgenios; Veniamin, Skevi; Pitta, Maria; Alevizopoulos, George (My University, 2021)
Τhe severity and variation of depressive symptoms (DS), among psychotic individuals under involuntary hospitalization is unclear. We investigated the socio-demographic and clinical characteristics of psychotic adults with DS involuntarily hospitalized for compulsory treatment in Cyprus. We also evaluated the psychometric properties (internal consistency, known-group and discriminant validity) of the HDRS-17 and HAM-A for the assessment of depressive and anxiety symptoms, respectively. A descriptive correlational study with cross-sectional comparisons was applied. Data on demographics, cognitive functioning (MoCA scale), depressive (HDRS-17 scale), anxiety (HAM-A scale) and psychotic (PANSS scale) symptoms were collected (December 2016 -February 2018). Following informed consent, the sample included 406 patients. Among them, 21 males and 23 females reported DS (HDRS-17 total score ≥8). The latter were mainly Greek-Cypriots (61.4%), 45-65 years old (38.6%), single (77.3%), unemployed (72.7%), mainly admitted due to aggressiveness towards others (47.7%), most frequently diagnosed with a bipolar disorder (59.1%). The mean score (M) in the HDRS-17 was 30.72 (scale range: 8-50; Standard Deviation [SD]: 10.42). The highest mean score (M) per item was in the variables "Suicide behavior"'(M:3.09; SD:1.09) and "Depressive mood" (M=2.95; SD=1.07). The DS group (HDRS-17 score≥8) reported higher PANSS positive symptoms subscale score (t-test, p=0.003) and HAM-A total score (t-test, p=0.05) compared to the non-DS group (HDRS-17 score<8). In multivariable logistic regression analysis only female sex [OR (95%CI) = 3.28 (1.33.-8.04), p=0.01)] and a mood disorder diagnosis [OR95% CI: 15.22(4.13.-56.14), p<0.0001)] retained a statistically significant association with DS. Cronbach' s alpha was 0.827 for the HDRS, and 0.763 for the HAM-A. The present findings partially support the known-group validity of the HDRS-17 and the ΗΑΜ-Α, and the discriminant validity of the HDRS-17 in psychotic patients under involuntary hospitalization. Additionally, the most frequent diagnosis in the DS group was a bipolar disorder, and the most frequent admission cause was aggressiveness towards others; it is possible that the majority of the DS group participants were patients with a bipolar disorder in episodes with mixed features, presenting simultaneously depressive symptoms and aggressiveness. Further studies on relapse prevention regarding this clinical group are proposed, as well as studies on specificity and sensitivity of the HDRS-17 and HAM-A.
Keywords: Depressive symptoms; Compulsory admission; Demographic characteristics; ΗΑΜ-Α; HDRS-17